Safety Climate and Turnover Intention in Border Areas: Insights from a Systematic Literature Review - Syarifah Novieyana; Maria Christiana Iman Kalis; M. Irfani Hendri (Information Technology and Science (ITScience), 2026)
Safety climate and turnover intention have become critical issues in organizational research due to their significant impact on employee well-being, operational effectiveness, and workforce sustainability. These issues are increasingly relevant in border areas, where workers face complex working conditions, including cross-border security threats, illegal activities, infrastructure limitations, and high psychological stress. The main objective of this study is to review and synthesize the literature on the issue of safety climate and turnover intention in border areas. There is a lack of research that focuses on border regions in particular, since most previous studies have focused on more conventional sectors like construction, hotels, and manufacturing, and have separated the impacts of safety climate on turnover intention. This study employs SLR models search reputable databases throughout the globe for relevant articles. The review focuses on studies addressing safety climate, leadership, organizational support, burnout, psychological well-being, and turnover intention in high-risk work environments. The results indicate that a positive safety climate significantly contributes to reducing burnout, emotional exhaustion, and turnover intention, while simultaneously enhancing employee well-being, organizational commitment, and safe work behavior. Leadership, organizational support, and digital transformation were also identified as key factors influencing workers’ perceptions of workplace safety. Furthermore, the border area environment exacerbates work-related stress due to geopolitical risks, security pressures, and technological challenges. This study concludes that strengthening the safety climate through adaptive leadership, organizational support, and digital safety systems is crucial for reducing turnover intention and supporting workforce sustainability in border areas.